Legal Environment, Technological Innovation, and Sustainable Economic Growth - Zhao, Yidan (Frontiers in Psychology, 2022)
The productivity gains generated by innovation are the root cause of long-term economic growth. In this paper, two empirical hypotheses are proposed to clarify our view: the trade turnover of technology market and intellectual property protection are important factors to stimulate innovation; The main channel of communication is through the increase of research staff and R&D funds. The empirical research result show that: (1) The greater the technology trade volume, the greater the incentive to regional innovation activities, the greater the number of regional patents; (2) About the intellectual property protection, The higher the protection intensity is, the greater the incentive is to regional innovation activities and the greater the number of regional patents. Different from relevant researches, this paper discusses the decisive role of market activity and legal environment on regional innovation behavior from the perspective of technology trade and patent protection, and emphasizes the theoretical significance of market and legal system from a more general perspective.